О биологическом значении окраски суслика крапчатого (Citellus suslicus Guld.) - Гиренко, Л.Л. (Вестник зоологии, 1967)
On the basis of carried observations concerning the behaviour of gopher Citellus-suslicus GuId. under natural and open-air cage conditions the colouration of these animals is noted to be of protective value only at the young age when hiding is the unconditioned reflex (instinct) — a reaction for danger. Grown-up gophers have this reflex suppressed by a chain of conditioned reflexes such as escape into their holes in case of danger. In this ontogenesis period the colouration loses its protective value because the moving animals are well noticeable for beasts. But the fact of appearance of conditioned reflexes and suppression of the instincts by them proves that they are more useful for the species than the instincts. Thus, not only morphological and ecologo-physiological peculiarities of animals are subjected to the age variability, but also ethological ones, expressed in the given case by various, corresponding to a certain age relations of behaviour and colouration and by the effect of their complex.